Design of Ecological CO2 Enrichment System for Greenhouse Production using TBAB + CO2 Semi-Clathrate Hydrate - Satoshi Takeya; Sanehiro Muromachi; Tatsuo Maekawa; Yoshitaka Yamamoto; Hiroko Mimachi; Takahiro Kinoshita; Tetsuro Murayama; Hiroki Umeda; Dong-Hyuk Ahn; Yasunaga Iwasaki; Hidenori Hashimoto; Tsutomu Yamaguchi; et al. (Energies, 2017)
This paper proposes an innovative CO2 enrichment system for crop production under a controlled greenhouse environment by means of tetra-n-butylammonium bromide (TBAB) + CO2 semi-clathrate hydrate (SC). In this system, CO2 is captured directly from exhaust gas from a combustion heater at night, which can be used for stimulating photosynthesis of crops in greenhouses during daytime. Although the gas capacity of TBAB + CO2 SC is less than that of CO2 gas hydrate, it is shown that TBAB + CO2 SC can store CO2 for CO2 enrichment in crop production even under moderate pressure conditions (<1.0 MPa) at 283 K.